Predictive Value of Routine Peripheral Blood Biomarkers in Alzheimer’s Disease - Dong, Xiaoyu; Nao, Jianfei; Shi, Jile; Zheng, Dongming (Frontiers in Aging Neuroscience, 2019)
Background: Biomarker screening is of major significance for the early diagnosis and prevention of Alzheimer's disease (AD). Routine peripheral blood parameters are easy to collect and detect, making them ideal potential biomarkers. However, there are few studies of biomarkers in peripheral blood with predictive or diagnostic value for AD. Routine blood parameters were studied in our cognitive impairment clinic. Method: We enrolled 56 AD patients, 57 mild cognitive impairment (MCI) patients, and 59 healthy elderly controls. Receiver operating characteristic (ROC) curves were used to assess the diagnostic values of routine blood biomarkers in patients with cognitive impairment. Results: There were significant differences in eight parameters between the groups. Logistic regression revealed that the neutrophil% (odds ratio [OR] 1.34, 95% confidence interval [CI] 1.03–1.75, p = 0.031) and neutrophil-to-lymphocyte ratio (NLR; OR 6.27, 95% CI 3.98–9.82, p = 0.003) differentiated AD patients and controls (areas under the curve [AUCs], 0.728 and 0.721) and that the NLR (OR 1.93, 95% CI 1.07–3.47, p = 0.028) and mean platelet volume (OR 1.67, 95% CI 1.04–2.70, p = 0.036) differentiated MCI patients and controls (AUCs, 0.60 and 0.638). There were no effective diagnostic biomarkers to distinguish AD from MCI. Conclusions: Some routine blood biomarkers may correlate with cognitive impairment. Analysis of these biomarkers, such as the NLR, may be useful for the identification of patients with cognitive impairment.